Prispevek k poznavanju prehrane pegaste sove Tyto alba na Ljubljanskem barju in v Sečoveljskih solinah - Sedmak, Ksenja (Acrocephalus, 2000)
The article discusses the Barn Owl's feeding habits at Ljubljansko barje (C Slovenia) and Sečovlje Salina (SE Slovenia) investigated with the method of pellet analysis. In pellets from Ljubljansko barje shrews were prevalent, while in respect of biomass common vole played an important role, too. The most preyed species by number and by biomass at Sečovlje Salina was Apodemus sylvaticus. Since owl is an opportunistic predator, results reflect differences in the environmental conditions in the hunting grounds at the two localities. The pellets found at Ljubljansko barje were on average larger thanthe ones found at Sečovlje Salina and also contained more prey units.
Keywords: bird; Birds; ptice; sove; Animal nutrition; food; prehrana